Interacting with Information in a Digital Place: Information Practices in World of Warcraft - Whippey, Caroline (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This study examines the ways in which users interact with information in the video game World of Warcraft. Utilizing data gathered through participant observation and the recording of public chat, this presentation explores how information is presented as well as how players seek, share, and utilize the information they encounter. Cette étude examine l’interaction des usagers avec l’information dans le jeu vidéo World of Warcraft. L’analyse de données recueillies par l’observation des participants et l’enregistrement de séances de clavardage publiques permet d’explorer comment l’information est présentée et comment les joueurs recherchent, partagent et utilisent l’information qui leur est présentée.